Modelling manufacturing employees’ performance based on a system dynamics approach - Alefari, Mudhafar; Fernández Barahona, Angel María; Salonitis, Konstantinos (Elsevier, 2018)
Employee performance is a key factor for the success of any modern organization. Employees are an asset that cannot be imitated by the competition, and therefore should be considered the most valuable resource. Unfortunately, they are also the hardest to control. Previous studies in manufacturing organizations have proven this. Performance improvement initiatives with a wide range of approaches are used in an attempt to improve employee performance. Motivation or organizational commitment are some examples of such programmes. However, the clear majority do not focus on the bigger picture. A conceptual model through system dynamics of the factors that affect employee performance and the different improvement initiatives is presented in this paper.
Keywords: continuous improvement; employee performance; system dynamics